Structure for planning in youth Olympic wrestling through the integrated macrocycle with accented loads - an alternativegomez - Noriega Gómez, J. C.; Ibanez Diaz, R. E. (International Journal of Wrestling Science, 2022)
The present investigation arises from the need presented by the Olympic Wrestling coaches of the youth category (16-18 years) of the Schools of Sports Initiation Schools (EIDE) to organize the structure of the training of their teams. Its objective was to design a structure for the planning of training in the youth category of Greco-Roman Wrestling through the Integrated Macrocycle model, the design of this scientific result is based on contemporary conceptions of accentuation of the load in the organization of sports training. Methods of the theoretical level, the analysis of documents, the systemic approach, the survey and the criteria of specialists were used. The designed planning structure was submitted to the criteria of specialists, who endorsed its possible application in practice.